Innovation diffusion in healthcare: evaluating the 'post-treatment' approach in Indonesia - Patrisia, Novliza Eka; Warsono, Hardi; Kismartini, Kismartini; Shinta Dewi, Reni (International Journal of Public Health Science (IJPHS), 2024)
This article aims to describe and qualitatively analyze the diffusion of innovation in healthcare services, specifically focusing on post-treatment healthcare services in the city of Bengkulu, Indonesia. Based on the innovation diffusion theory and incorporating the theory of reasoned action (TRA), this research explores behavior in the process of organizing and implementing healthcare services to enhance the quality of public services in Bengkulu. The study employs a qualitative descriptive research approach, utilizing data sources such as interviews, direct field observations, and documentation. The results of this study indicate that knowledge serves as the primary foundation in the diffusion of innovation in healthcare services. In the context of post-treatment services, the community lacks knowledge about these services. The findings of this research are expected to provide insights for the local government of Bengkulu, particularly Harapan dan Doa Hospital (RSHD) in Bengkulu, as a healthcare service provider. Through knowledge dissemination among all stakeholders supporting innovation diffusion, each can play their respective roles. Consequently, with knowledge playing a key role in the diffusion of innovation in healthcare services, it is anticipated that it will enhance the quality of healthcare services through effective and efficient service delivery, with a focus on the goals of innovation.